KRISIS MORAL DALAM KARYA SENI LUKIS SUREALIS - Erik Darma Utama; Erfahmi Erfahmi (Universitas Negeri Padang, 2020)
This work was made for the purpose of visualizing the state of the current moral crisis in surrealist paintings, in the hope that humans would become more aware of their current moral crisis. The methods used in the process of this final work are: 1) Preparation, 2) Elaboration, 3) Synthesis, 4) Realization of Concepts, 5) Completion. With the behavior, actions, and human nature that is getting worse which causes various problems in him, the environment, and the surrounding community. This final work totals ten works with the title: What Is Tomorrow Like, All Our Acts, The Last Tree, About The House, Seeing But Not Touching, A Heart, Above The Wind, Value At Difference, Toy Heroes, Rumors.Keywords: Moral, Painting, Surreal